Wi-Fi Enabled Healthcare - Youssef, Ali (Taylor & Francis, 2014)
Focusing on its recent proliferation in hospital systems, Wi-Fi Enabled Healthcare explains how Wi-Fi is transforming clinical work flows and infusing new life into the types of mobile devices being implemented in hospitals. Drawing on first-hand experiences from one of the largest healthcare systems in the United States, it covers the key areas associated with wireless network design, security, and support. Reporting on cutting-edge developments and emerging standards in Wi-Fi technologies, the book explores security implications for each device type. It covers real-time location services and emerging trends in cloud-based wireless architecture. It also outlines several options and design consideration for employee wireless coverage, voice over wireless (including smart phones), mobile medical devices, and wireless guest services. This book presents authoritative insight into the challenges that exist in adding Wi-Fi within a healthcare setting. It explores several solutions in each space along with design considerations and pros and cons. It also supplies an in-depth look at voice over wireless, mobile medical devices, and wireless guest services. The authors provide readers with the technical knowhow required to ensure their systems provide the reliable, end-to-end communications necessary to surmount today's challenges and capitalize on new opportunities. The shared experience and lessons learned provide essential guidance for large and small healthcare organizations in the United States and around the world. This book is an ideal reference for network design engineers and high-level hospital executives that are thinking about adding or improving upon Wi-Fi in their hospitals or hospital systems.